2001
DOI: 10.1038/oby.2001.101
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation and Obesity in Australian Women: A Prospective Study

Abstract: Genetic variation and obesity in Australian women: a prospective study. Obes Res. 2001;9:733-740. Objective: A number of candidate genes have been implicated in the pathogenesis of obesity in humans. This study examines associations between longitudinal changes in body mass and composition and the presence of polymorphisms in the ␤-3 adrenergic receptor, tumor necrosis factor-␣, leptin, and leptin receptor (Lepr) in a cohort of Australian women. Research Methods and Procedures: Healthy white Australian women (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 32 publications
0
11
0
2
Order By: Relevance
“…29 Several studies have reported that people with this SNP showed an increased risk of developing obesity and glucose intolerance, 32,33 whereas other studies failed to find any correlation between this mutation and body mass index. 45,46 The results for ApoC3 -455 were also not consistent with those of the Italian cohort, which showed an association of the 4 Kruskal-Wallis test. 5 The first measurement after patients started antiretroviral therapy.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…29 Several studies have reported that people with this SNP showed an increased risk of developing obesity and glucose intolerance, 32,33 whereas other studies failed to find any correlation between this mutation and body mass index. 45,46 The results for ApoC3 -455 were also not consistent with those of the Italian cohort, which showed an association of the 4 Kruskal-Wallis test. 5 The first measurement after patients started antiretroviral therapy.…”
Section: Discussionmentioning
confidence: 65%
“…Almost half of the patients started ART immediately after being diagnosed with HIV infection. Median CD4 count per microliter pre-ART was 45 and that post-ART (after 1 year) was 210.5. The mean followup period was 4.85 years (SD = 2.42).…”
Section: Incidences Of La And/or Ld In Hiv-1-infected Thai Patients Umentioning
confidence: 99%
“…For instance, while the Pro1019Pro Lepr polymorphism in particular associated with both high adiposity and longitudinal gains in BMI (de Silva et al 2001) there are some studies proposing additional genes (e.g. APO-E gene, the uncoupling protein 1 gene and the B3-adrenergic receptor gene polymorphisms) as specific regulators of longitudinal increments in adult body weight (Gueguen et al 1989;Sivenius et al 2000;Clement et al 1995).…”
Section: Discussionmentioning
confidence: 97%
“…This is supported as well by several observations at the molecular level. For instance, although the Pro1019Pro Lepr polymorphism is particularly associated with both high adiposity and longitudinal gains in BMI,38 there are some studies proposing additional genes (eg APO-E gene, the uncoupling protein 1 gene and the B3-adrenergic receptor gene polymorphisms) as specific regulators of longitudinal increments in adult body weight 39 – 41. Yet, these specific genes have not been widely replicated as predictors of long-term weight gain.…”
Section: Discussionmentioning
confidence: 99%